Bandwidth allocation policy using the game theory model in heterogeneous wireless networks - Anwar, Farhat; Masud, Mosharrof Hussain; Khan, Burhan Ul Islam; Olanrewaju, Rashidah Funke; Abdul Latif, Suhaimi (International Publisher for Advanced Scientific Journals (IPASJ), 2018)
Bandwidth aggregation in heterogeneous wireless networks (HWN) can be one of the effective solutions in providing quality data transmission for real-time applications. However, transmitting the data through multiple networks create packet reordering issues that result in transmission delay and degrades the overall quality of services. This paper addresses packet reordering issues both for single and multiple paths with a reordering delay in the transmission system. An algorithm has proposed to mitigate the associated delay that has been simulated in network simulator 3 (NS3). The simulation results have benchmarked with the well known Earliest Delivery Path First (EDPF) method and shown better performance over the EDPF results. Moreover, the simulation has been done to analyze the packet scheduling including to measuring packet reordering delay, and reordering entropy. CBR and VBR applications have been transmitted for 1800ms from sender to receiver in a heterogeneous wireless environment created in NS3. The results show the proposed method achieved to reduce the reordering delay and reordering entropy both for CBR and VBR applications.